$X$-permutable maximal subgroups of Sylow subgroups of finite groups - Guo, W.; Skiba, A. N.; Shum, K. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We study finite groups whose maximal subgroups of Sylow subgroups are permutable with maximal subgroups.